EFEKTIVITAS STORYTELLING MARKETING DAN KUALITAS PELAYANAN TERHADAP PURCHASE DECISION DENGAN TRUST SEBAGAI VARIABEL MEDIASI (Pada Survey Pelanggan Indihome Kota Padang) - Rezky Mulia Armus; Eri Besra; Suziana (Journal Publicuho, 2025)
This study aims to analyse the effect of storytelling marketing and service quality on purchase decisions with trust as a mediating variable among IndiHome customers in Padang City. The study employed purposive sampling with a total sample of 195 respondents who had subscribed to IndiHome for at least 6 months. Data analysis was conducted using the Structural Equation Modelling (SEM) method based on Partial Least Square (PLS) with the assistance of SmartPLS 4.0 software. The results show that storytelling marketing does not have a significant effect on purchase decisions. Conversely, service quality has a positive and significant effect on purchase decisions. Furthermore, both storytelling marketing and service quality have a positive and significant effect on trust. Trust also has a positive and significant impact on purchase decisions, mediating the influence of storytelling marketing and service quality on these decisions. The coefficient of determination (R²) value for the trust variable is 0.683, which means that 68.3% of the variation in trust can be explained by storytelling marketing and service quality. Meanwhile, the R² value for subscription decisions is 0.677, which means that 67.7% of the variation in subscription decisions can be explained by storytelling marketing, service quality, and trust. The remaining 32.3% is explained by other factors outside the scope of this study.